Effects of Blood Pressure Control in Cardiovascular Prevention - Artom, Nathan; Vecchie, Alessandra; Pende, Aldo (Current Pharmaceutical Design, 2016)
Background: High blood pressure is the main risk factor worldwide for mortality and morbidity. Subjects with uncontrolled hypertension increased in the last decades. Methods: This review is based on the material searched for and obtained via MEDLINE and PubMed up to June 2016. The search terms used were “hypertension, blood pressure control” in combination with “pathophysiology, lifestyle, antihypertensive drugs, target organ damage, target values and comorbidity”. Results: This narrative review focused its attention on the diagnosis, the pathophysiology, the clinical consequences of arterial hypertension, and on the factors that must be considered for a better blood pressure control. In fact, the attainment of an adequate blood pressure control is a challenge at both a population and an individual level. Conclusion: The review will discuss the best strategy to reduce uncontrolled hypertension and cardiovascular events in hypertensive patients identifying the main conditions which determine and maintain uncontrolled hypertension also highlighting the new possible strategies for a better blood pressure control and including the results of very recent multicenter randomized controlled trials.
Keywords: pathogenesis